FOR A BETTER TEACHING OF DANCE ON PHYSICAL EDUCATION CLASSES : A THOUGH ABOUT THE MOVEMENT LIVED THOUGH DANCE (Fiep Bulletin - online, 2015)
Physical education, once an area of knowlogment that studies movement, is directly involved with corporal and social questions in which human being is inserted. Based by human movement, it is in charge to comprehend the man as constructor of an identity socio-cultural. Factors that contributes to a better performance of the professional during his classes were noted when body was related with society. This is due to knowlogment and history that the physical body presence on the classroom brings, leading the teacher realize the student's neediness and objectives.  Education, once inserted to knowlogment and human being graduation on society elucidate the needing of expressive activities as way to feel and interpret  quotidian situation.Purposing to body the sensation that the movement provides on space, gives meaning to corporal expressions presented on men quotidian. Dance, presented on physical education, is not only motor capacity, besides contributing a lot to human potential development, the dance mainly, excites on the student a relation person-world, leading to construction of a  conscious and reflexive person about his relation with body and society.The movement, full of sensations and expressions , represents the signal of an identity presented on society that is justified due to the junction of pscicosocial, cultural and biological aspects that compose individual characteristics of each human being. Those aspects presents on social development, intensify the movement function as educative purpose on the dance practice, showing that is important to create conditions for relation with people and the world, body knowlogment and its potentialities, cognitive evolution and self-control for interpretation and question aments presents in the world.
Keywords: Dance; movement; education.